Comparison of 5 monoclonal antibodies for immunopurification of human butyrylcholinesterase on Dynabeads: KD values, binding pairs, and amino acid sequences. (5th October 2015) - Peng, Hong; Brimijoin, Stephen; Hrabovska, Anna; Targosova, Katarina; Krejci, Eric; Blake, Thomas A.; Johnson, Rudolph C.; Masson, Patrick; Lockridge, Oksana
Abstract: Human butyrylcholinesterase (HuBChE) is a stoichiometric bioscavenger of nerve agents and organophosphorus pesticides. Mass spectrometry methods detect stable nerve agent adducts on the active site serine of HuBChE. The first step in sample preparation is immunopurification of HuBChE from plasma. Our goal was to identify monoclonal antibodies that could be used to immunopurify HuBChE on Dynabeads Protein G. Mouse anti-HuBChE monoclonal antibodies were obtained in the form of ascites fluid, dead hybridoma cells stored frozen at −80 °C for 30 years, or recently frozen hybridoma cells. RNA from 4 hybridoma cell lines was amplified by PCR for determination of their nucleotide and amino acid sequences. Full-length light and heavy chains were expressed, and the antibodies purified from culture medium. A fifth monoclonal was purchased. The 5 monoclonal antibodies were compared for ability to capture HuBChE from human plasma on Dynabeads Protein G. In addition, they were evaluated for binding affinity by Biacore and ELISA. Epitope mapping by pairing analysis was performed on the Octet Red96 instrument. The 5 monoclonal antibodies, B2 12-1, B2 18-5, 3E8, mAb2, and 11D8, had similar KD values of 10 −9  M for HuBChE. Monoclonal B2 18-5 outperformed the others in the Dynabeads Protein G assay where it captured 97% of the HuBChE in 0.5 ml plasma. Pairing analysis showed that 3E8 and B2 12-1 share the same epitope, 11D8 and B2 18-5 share the same epitope, but mAb2 and B2 12-1 or mAb2 and 3E8 bind to different epitopes on HuBChE. B2 18-5 was selected for establishment of a stable CHO cell line for production of mouse anti-HuBChE monoclonal. Highlights: Sequences of 4 mouse anti-HuBChE monoclonals determined from DNA amplicons. Monoclonals have nanomolar KD values. Pairing analysis identified monoclonals for sandwich assays. CHO cell line secretes monoclonal B2 18-5 for immunopurification of HuBChE.